Post-cat Bite Septic Arthritis Of The Hand Caused By Pasteurella Multocida - N A Mohamed; Z Z Rashid; S A Rhani (Internet Scientific Publications, 2024)
We report a case of Pasteurella multocida infection which developed into septic arthritis. The patient was a 25-yearold Malay male who developed fever with abscess formation at the second and third web space of his right hand and septic arthritis involving the metacarpophalangeal joint of the right middle finger and ring finger after he was bitten by a dying stray cat. The organism was isolated in pure culture from pus and tissue specimens from the joint cavity and web spaces, and identified as Pasteurella multocida. The patient responded to a 1-week course of intravenous amoxicillin-clavulanate therapy, was discharged home with a 6-week dose of oral amoxicillin-clavulanate and had an uneventful recovery. Management of cat bites involve early, thorough wound irrigation, plus wide-spectrum empiric antibiotics such as amoxicillin-clavulanate and later guided by culture results. A radiograph is indicated to rule out the presence of foreign body or teeth fragments, as well as fractures or bone involvement. Surgical debridement and drainage is required in established infections, to remove devitalised tissue and any foreign bodies in order to prevent the sequelae of infection and long-term morbidity.